Progress in Continuous Flow Synthesis of Hydrogen-Bonded Organic Framework Material Synthons - Xingjun Yao; Sanmiao Wen; Ningning Ji; Qiulin Deng; Zhiliang Li; Hongbing Wang; Qianqian Shang (Molecules)
Hydrogen-bonded organic framework (HOF) materials are typically formed by the self-assembly of small organic units (synthons) with specific functional groups through hydrogen bonding or other interactions. HOF is commonly used as an electrolyte for batteries. Well-designed HOF materials can enhance the proton exchange rate, thereby boosting battery performance. This paper reviews recent advancements in the continuous synthesis of HOF synthons, in the continuous synthesis of HOF’s unit small molecules enabling the multi-step, rapid, and in situ synthesis of synthons, such as carboxylic acid, diaminotriazine (DAT), urea, guanidine, imidazole, pyrazole, pyridine, thiazole, triazole, and tetrazole, with online monitoring. Continuous flow reactors facilitate fast chemical reactions and precise microfluidic control, offering superior reaction speed, product yield, and selectivity compared to batch processes. Integrating the continuous synthesis of synthons with the construction of HOF materials on a single platform is essential for achieving low-cost, safe, and efficient processing, especially for reactions involving toxic, flammable, or explosive substances.